Pengaruh Atribut Halal Terhadap Keputusan Pembelian Kosmetik Wardah: (Survey Pada Karyawan PT. Barclay Products Jakarta) - Paska Maria; Pandoyo (CV ODIS, 2020)
This study aims to determine the effect of the Halal attribute on purchasing decisions for Wardah cosmetics on employees of PT. Barclay Products Jakarta. In the midst of consumers' concerns over the ingredients in cosmetic products, Wardah is here to prioritize natural and halal ingredients as their advantages. This type of research is field research (field research), namely direct observation of the object under study in order to obtain relevant data. Data collection techniques are by distributing questionnaires and interviews. The data analysis technique used is descriptive and quantitative. Primary data were obtained from a questionnaire/list of statements and processed using SPSS 18.0. The results showed that the Halal Attribute had a significant effect on Purchase Decisions with an affect value of 43.2%. Suggestions in this research are that companies should still include halal attributes on all their products and add halal label inclusion for products that have not received a halal label through LPPOM MUI and health experts